2020
DOI: 10.1108/intr-03-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-esteem, conscientiousness and pseudo-personality on technostress

Abstract: PurposeThe authors investigated how personality traits are associated with workplace technostress (perception of stressors related to the use of information and communication technologies (ICTs).Design/methodology/approachThe authors collected 95 self-rated and 336 observer-rated questionnaires using the personality audit and a shortened version of the technostress scale. To analyze relationships between personality dimensions and technostress, the authors applied partial least squares structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…the home environment). But the current literature on technostress ( Tarafdar et al, 2019 , Khedhaouria and Cucchi, 2019 , Korzynski et al, 2020 , Yener et al, 2020 ) has offered little in terms of comparative assessment of these two different types of technostress. Drawing on theoretical lenses of the stressor-strain-outcome ( Ragu-Nathan et al, 2008 ) and resource-experiences-demands models ( Salanova et al, 2011 ), we address this research gap by merging the two parallel but related streams of research on technostress.…”
Section: Methodsmentioning
confidence: 99%
“…the home environment). But the current literature on technostress ( Tarafdar et al, 2019 , Khedhaouria and Cucchi, 2019 , Korzynski et al, 2020 , Yener et al, 2020 ) has offered little in terms of comparative assessment of these two different types of technostress. Drawing on theoretical lenses of the stressor-strain-outcome ( Ragu-Nathan et al, 2008 ) and resource-experiences-demands models ( Salanova et al, 2011 ), we address this research gap by merging the two parallel but related streams of research on technostress.…”
Section: Methodsmentioning
confidence: 99%
“…Technostress research has used the techno-stressors defined by Tarafdar et al ( 2011 ) or Ayyagari et al ( 2011 ) to analyze their work-related antecedents and consequences. In terms of antecedents, studies have found different organizational environments (e.g., decision centralization; Wang et al 2008 ), job characteristics (e.g., job autonomy; Suh & Lee, 2017 ), technology features (e.g., complexity; Qi, 2019 ), and personal characteristics, such as demographics (e.g., age or gender; Marchiori et al 2019 ), attitudes (e.g., dispositions to job; Bala and Bhagwatwar 2018 ), personality (e.g., extraversion; Korzynski et al 2020 ), or cultural values (Ma and Turel 2018 ), to be drivers of technostress. In terms of consequences, technostress produces strain (Galluch et al 2015 ; Lee et al 2016a ) and affects negatively other outcomes, such as technology end-user satisfaction (Fuglseth and Sørebø 2014 ; Tarafdar et al 2011 ; Tu et al 2008 ), job satisfaction (Jena 2015 ; Kumar et al 2013 ; Ragu-Nathan et al 2008 ), performance (Ioannou and Papazafeiropoulou 2017 ; Jena 2015 ; Li and Wang 2021 ), and organizational commitment (Jena, 2015 ; Tarafdar et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes linked to technostress are called strain responses and can be psychological, behavioral or physiological (Ayyagari et al, 2011;Ragu-Nathan et al, 2008). Studies conclude that people reporting elevated levels of technostress are more likely to suffer the psychological strains of diminished commitment (Tarafdar et al, 2010(Tarafdar et al, , 2015, poor selfesteem (Korzynski et al, 2020), dissatisfaction with the IT system (Tams et al, 2020), harmful psychological responses (Riedl et al, 2012), burnout (Afifi et al, 2018) and lower job satisfaction (Califf and Sarker, 2020;Suh and Lee, 2017). While studies of technostress generally rely on self-reported data, physiological studies have also demonstrated that stress hormones cortisol and alpha amylase increase with IT-mediated interruptions (Tams et al, 2018), IT system breakdown (Riedl et al, 2012) and extensive exposure to IT applications (Afifi et al, 2018).…”
Section: Effect Of Sns On Academic Achievementmentioning
confidence: 99%